Ionizing Radiation Technologies for Vaccine Development - A Mini Review - Bhatia, Sohini S.; Pillai, Suresh D. (Frontiers in Immunology, 2022)
Given the current pandemic the world is struggling with, there is an urgent need to continually improve vaccine technologies. Ionizing radiation technology has a long history in the development of vaccines, dating back to the mid-20th century. Ionizing radiation technology is a highly versatile technology that has a variety of commercial applications around the world. This brief review summarizes the core technology, the overall effects of ionizing radiation on bacterial cells and reviews vaccine development efforts using ionizing technologies, namely gamma radiation, electron beam, and X-rays.